Histological and physiological study of the negative influences of the toxins secreted by Aspergillus flavuis on the fertility of male albino rats - Ahmed J. Al-Naaly et.al (Al-Qadisiyah Journal of Pure Science, 2017)
The present study aims to determine influences exudation liquid culture of Aspergillus flavus separated from yellow corn seeds infection with fungus which was given to animals at the dose (20 ml/kg) of body weight on body weight ,testis and epididymis weight , some sperm parameter (Total sperm count , percentage of movable sperms and it's activity degree and percentage of normal and abnormal sperms) and measurement concentration of some reproductive hormones (testosterone, FSH, LH) as well as histological study which include: the counting of spermatogenesis cells and leydig cells.Experimental included (20) male albino rats randomly divided into equal two groups :control group and treated group. The animals were exposure to the same condition of temperature ,light and diet along the experiment. After end of experiment the animals were Weighted and anesthetized, the blood was draw from heart directly, to measurement concentration hormones. The animals were dissecting and the testis and epididymis were ablated to weight and to preparation of histological slide.Result showing significant decreases (P<0.05) of body weight, testis/body weight ratio , epididymis weight/ body weight ratio, total sperm count , percentage of movable sperms and it's activity degree , percentage of normal and abnormal sperms as well as the significant decreases in concentration of testosterone, FSH and LH hormone in treated group with A. flavuis comparative with control group.On the other hand, The histological changes revealed significant decreases (P<0.05) in the mean of spermatogenesis cells and leydig cells.